Outcome of Nursing Practice Guidelines for COVID –19 Patients at the Emergency Department, Sakon Nakhon Hospital - Nakain, Patcharin (Medical Journal of Sakon Nakhon Hospital, 2024)
This quasi–experimental research aimed to study the outcome of nursing practice guidelines for COVID–19 patients at the emergency department, Sakon Nakhon hospital. The samples recruited by purposive sampling were 31 registered nurses who had duty on nursing care of COVID–19 infected patients visited at the emergency department. The instruments consisted of nursing practice guidelines for COVID–19 patients with a reliability of 0.83 as determined by the Cronbach’s alpha coefficient. The study was conducted using one group pretest–posttest design from November to December, 2022. The data were analyzed using the descriptive statistics, frequency, percentage, mean and standard deviation. The result showed that the overall practice according to the nursing practice guideline for COVID–19 patients was in the excellent level = 4.59, S.D. = 0.71). The advice for self–care at home aspect had the highest mean score ( = 4.63, S.D. = 0.64), followed by the nursing care in the negative pressure room ( = 4.59, S.D. = 0.78) and COVID–19 screening desk ( = 4.55, S.D. = 0.66), respectively. The overall satisfaction with nursing practice guidelines for COVID–19 patients was in the high level ( = 4.00, S.D. = 0.58). The COVID–19 infected rate among service provider before guideline implementation was 29% but it was not found after this guideline implementation. This study suggested the compliance of nursing practice guideline for COVID–19 patients in emergency department, Sakon Nakhon hospital effectively prevented the spread of COVID–19 infection among service provider. Therefore, this nursing practice guideline should be further applied to another department.